Nidogen-2 (NID2) is a Key Factor in Collagen Causing Poor Response to Immunotherapy in Melanoma - Sha Y; Mao AQ; Liu YJ; Li JP; Gong YT; Xiao D; Huang J; Gao YW; Wu MY; Shen H (Dove Medical Press, 2023)
Yan Sha,1,* An-qi Mao,1,* Yuan-jie Liu,2 Jie-pin Li,2 Ya-ting Gong,3 Dong Xiao,1 Jun Huang,1 Yan-wei Gao,1 Mu-yao Wu,3 Hui Shen1 1Departments of Dermatology, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, People's Republic of China; 2Department of Oncology, Affiliated Hospital of Nanjing University of Chinese Medicine, Jiangsu Province Hospital of Chinese Medicine, Nanjing, People's Republic of China; 3Departments of Rehabilitation, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Zhangjiagang, People's Republic of China*These authors contributed equally to this workCorrespondence: Hui Shen; Mu-yao Wu, Email zjgzy046@njucm.edu.cn; wumuyao0613@163.comBackground: The incidence of cutaneous melanoma continues to rise rapidly and has an extremely poor prognosis. Immunotherapy strategies are the most effective approach for patients who have developed metastases, but not all cases have been successful due to the complex and variable mechanisms of melanoma response to immune checkpoint inhibition.Methods: We synthesized collagen-coding gene expression data (second-generation and single-cell sequencing) from public Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases. Bioinformatics analysis was performed using R software and several database resources such as Metascape database, Gene Set Cancer Analysis (GSCA) database, and Cytoscape software, etc., to investigate the biological mechanisms that may be related with collagens. Immunofluorescence and immunohistochemical staining were used to validate the expression and localization of Nidogen-2 (NID2).Results: Melanoma patients can be divided into two collagen clusters. Patients with high collagen levels (C1) had a shorter survival than those with low collagen levels (C2) and were less likely to benefit from immunotherapy. We demonstrated that NID2 is a potential key factor in the collagen phenotype, is involved in fibroblast activation in melanoma, and forms a barrier to limit the proximity of CD8+ T cells to tumor cells.Conclusion: We clarified the adverse effects of collagen on melanoma patients and identified NID2 as a potential therapeutic target.Keywords: Skin Cutaneous Melanoma, collagen molecules, NID2, bioinformatics, immunotherapy